Gross Domestic Product and Health Expenditure Growth in Balkan and East European Countries—Three-Decade Horizon - Stepovic, Milos; Rancic, Nemanja; Vekic, Berislav; Dragojevic-Simic, Viktorija; Vekic, Stefan; Ratkovic, Nenad; Jakovljevic, Mihajlo (Frontiers in Public Health, 2020)
Background: Dynamics of health care has changed over the time along with development of the countries themselves. The aim of the study is to compare macroeconomic and health expenditure indicators of interest, such as Total health expenditure (THE) as percent of global domestic product; global domestic product per capita in US$ and Private households' out-of-pocket payments of Balkan and East Europe countries on health, as well as to assess their progress over the observed period. Methods: This research report article represents the descriptive data analysis of indicators extracted from European Health for all database. The data was analyzed using a linear trend and regression analysis to estimate the timeline changes. Results: Greece and Slovenia have the largest median values of global domestic product per capita throughout the whole period and the largest increment trend was in Lithuania. Median value in out-of-pocket payment of total health expenditure was the highest in Albania and Ukraine, while the largest decrease in trend was noticed in Albania and Bosnia and Herzegovina. The largest median value of THE as percent of GDP in the observed period had Bosnia and Herzegovina and Greece, while regression trend analysis showed that the largest increase had Serbia. Most of the countries showed significant correlation between observed indicators. Conclusion: Trends in the economy must be constantly monitored due to the fact that the population is aging and non-communicable diseases are multiplying, which requires innovations in medical treatments and pharmaceutical developmentions.